ANALISIS KUALITAS BUTIR SOAL PILIHAN GANDA PENILAIAN AKHIR TAHUN (PAT) GENAP BERORIENTASI HOTS TEMA 6 KELAS V DI SD NEGERI PAGEDANGAN ILIR - Novita, Wulan (Didaktika, 2022)
The purpose of this study is to see the quality of the items in theme 6 for fifth grade and this is based on a review of the validity of the questions, the reliability of the questions, the level of difficulty, discriminating power and effectiveness of distractors and to find out whether the questions of theme 6 are Higher Order Thinking Skill-oriented. Questions are declared good if they meet the conditions that have been set. Thinking is an activity in which a person manages his memory to solve a problem. This study uses a mixed method or mixed method, in which this mixed method connects qualitative and quantitative techniques in one study. The data collection technique uses documentation, namely collecting student answer sheets on theme 6 and the technique then the questions are then analyzed to determine the validity, reliability, discriminating power, level of difficulty, and effectiveness of the distractors using the Anates Version 4 application. using Bloom's Taxonomy table. Based on the analysis of the questions, there are 4 questions (20%) in the very good category, 4 questions (20%) in the good category, 5 questions (25%) in the very good category, 5 questions (25%) in the bad category and 2 items in the multiple choice theme. 6 bad categories. Based on the HOTS study of multiple choice items, Theme 6 of the 20 questions submitted based on Operational Verbs used in Bloom's taxonomy include 7 questions in group C1 (Knowing), 5 questions in group C2 (Understanding), 2 items questions in group C3 (Applying), 4 questions in group C4 (Analyzing) and 2 items in group C5 (Evaluating) there are no questions that are included in group C6 (Creating). So, out of 20 HOTS-oriented questions, there are 6 questions.